The Production Efficiency in Organic Rice Farming - Galuh Pawitri; Kustopo Budiraharjo; Bambang Mulyatno Setiawan (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The production efficiency in farming must be achieved so that production was high and farmers' income increased. The aim of this research was to analyze the influence of the production factors used on the production of organic rice farming and to analyze the efficiency of production. The research was conducted by using a survey method with 79 farmers as respondents. The research location was in Jetis Village, Sambirejo Sub-district, Sragen Regency. The analysis tool used multiple linear regression and efficiency test. The results showed that the use of production factors had a significant effect simultaneously and partially, except for fertilizer production factors. Organic rice farming in Jetis Village was technically inefficient. In allocative terms, the use of land area, seeds, pesticides and labor was not yet efficient, while fertilizers were not efficient. Economically, the use of land area, seeds and pesticides was not yet efficient, while fertilizers and labor were not efficient.